Henry Clay and the War of 1812 - King, Quentin Scott, 1924- (McFarland & Company, Inc., Publishers, 2014)
"Any biography of Henry Clay's 46 year political career quickly becomes entangled with his monumental, though youthful, political leadership of the War Hawks in urging the Madison Administration to arm the United States for war with Great Britain. There has been no detailed treatment of his major role in this early American war until this present work"--